La poesia en la prosa de Joan Roís de Corella: delimitació i transmissió del corpus. - LLUÍS MARTOS, JOSEP (Scripta, 2019)
The work in prose by Joan Roís de Corella is characterized by the incorporation of poetry. In this sense, this work has a double objective, which is marked by its title. On the one hand, it delimits the corpus, which is able to catalog twenty-one poems, from a very diverse extent, from one vers up to twenty-eight. On the other hand, it studies the textual transmission of these poems, paying special attention to the features that characterize the different testimonies and to the particularities of transmission of poems.